Nanoparticles from Cu-Zn-Al shape memory alloys physically synthesized by ion milling deposition - López Pavón, Luis Alberto; López Cuéllar, Enrique Manuel; Ballesteros, Carmen; Torres Castro, Alejandro; Martínez de la Cruz, Azael; Araújo, Carlos José de (2012)
In this research, an ion milling equipment was used to elaborate nanoparticles from Cu-Zn-Al alloys with shape memory effect. Two different compositions were used, target A: 75.22Cu-17.12Zn-7.66Al at % with an Ms of –9 °C and target B: 76.18Cu-15.84Zn-7.98Al with an Ms of 20 °C. Nanoparticles were characterized by High Resolution Transmission Electron Microscopy, Electron Diffraction and Energy Dispersive X-ray Spectroscopy. The obtained nanoparticles showed a small dispersion, with a size range of 3.2-3.5 nm. Their crystal structure is in good agreement with the bulk martensitic structure of the targets. In this sense, results on morphology, composition and crystal structure have indicated that it is possible to produce nanoparticles of CuZnAl shape memory alloys with martensitic structure in a single process using Ion Milling.